Relationship between pain and motor and non‐motor symptoms in Parkinson's disease. (18th May 2017) - Defazio, G.; Antonini, A.; Tinazzi, M.; Gigante, A. F.; Pietracupa, S.; Pellicciari, R.; Bloise, M.; Bacchin, R.; Marcante, A.; Fabbrini, G.; Berardelli, A.
Abstract : Background and purpose: Although female gender, depressive symptoms and medical conditions predisposing to pain are more common in patients with Parkinson's disease (PD) with pain, no study has yet explored the relationship between pain and other non‐motor symptoms (NMS). Methods: A total of 321 consecutive patients with PD [190 men/131 women aged 68.3 (SD 9.2) years] attending four Italian movement disorder clinics were studied. Demographic/clinical data were obtained by a standardized interview and the NMS scale. The association of pain with motor and NMS was assessed by multivariable logistic regression models. Results: At the time of the study, 180 patients with PD (56%) reported chronic pain that, in most cases, was described as being muscular or arthralgic pain. Pain preceded the onset of motor signs in 36/180 patients. In the main‐effect model, factors independently associated with pain were female sex [odds ratio (OR), 2.1; P = 0.01], medical conditions predisposing to pain (OR, 2.9; P < 0.001), Hoehn–Yahr staging (OR, 1.9; P = 0.04), motor complications (OR, 4.7; P = 0.04) and NMS belonging to the sleep/fatigue (OR, 1.6; P = 0.04) and mood/cognition (OR, 1.6; P = 0.03) domains. Most explanatory variables in the multivariable analysis were similarly distributed in patients in whom pain may have been related to PD or to a cause other than PD. Conclusions: We confirm that pain in PD is more frequent in women and in subjects with medical conditions predisposing to painful symptoms. Moreover, this strengthens the association between pain and motor severity measures and NMS domains, particularly sleep and mood disturbances.